Research on Temporal and Spatial Changes of Extreme Climate in Guangdong Province from 1961 to 2016 - HUANG Weijie; ZHANG Dawei; ZHANG Xin; LI Qingfeng; LI Wangming; WANG Yadi (Renmin Zhujiang)
Extreme climate has the most serious and destructive impact on natural ecosystems,socio-economic development,human health and biodiversity.This paper examines the spatial and temporal variability of climate extremes in Guangdong Province during the period 1961—2016.The results show that most of the extreme precipitation indicators remain consistent in the time series,but the maximum 5 day precipitation amount (RX5day) and the consecutive wet days (CWD) series mutate.Except for the diurnal temperature range(DTR),most of the extreme temperature indicators have abrupt changes in the time series.Except for CWD,all extreme precipitation indexes basically showed an insignificant upward trend;all extreme temperature indexes basically showed an upward trend in varying degrees,but DTR and growing season length (GSL) showed no significant downward trend.The main period of extreme precipitation index is in the range of 2.03~4.00 a;while the main period of extreme temperature index is in the range of 2.00~3.50 a.There are differences in the spatial distribution of extreme precipitation indicators and extreme temperature indicators,and each one has its own characteristics.